Challenges of Transarticular Screw Fixation in Young Children: Report of Surgical Treatment of a 5-Year-Old Patient's Unstable Os-Odontoideum - Takahashi, Jun (Asian Spine J, 2016)
Surgical procedures for atlantoaxial (C1–C2) fusion in young children are relatively uncommon. The purpose of this study was to report on a surgical treatment for a case of atlantoaxial instability caused by os-odontoideum in association with quadriparesis and respiratory paralysis in a 5-year-old girl. We present the patient's history, physical examination, and radiographic findings, describe the surgical treatment and a five year follow-up, and provide a literature review. The instability was treated by halo immobilization, followed by C1–C2 transarticular screw fixation using a computed tomography-based navigation system. At the five year follow-up, the patient had made a complete recovery with solid union. The authors conclude that C1–2 transarticular screw fixation is technically possible as in a case of atlantoaxial instability in a five-year-old child.